The Electrification of Russia, 1880-1926 - Coopersmith, Jonathan, 1955- (Book collections on Project MUSE., 1992)
Here is the first full account of the widespread adoption of electricity in Russia, from the beginning in the 1880s to its early years as a state technology under Soviet rule. Jonathan Coopersmith has mined the archives for both the tsarist and the Soviet periods to examine a crucial element in the modernization of Russia. Coopersmith's main interest is the social and political context of the new technology, and throughout his narrative he shows the principal effects of political change on the diffusion and adoption of technological innovation. Among the topics he covers are the early importance of the tsarist military to the electrification movement, the major role of international technology transfer, the ways in which tsarist policies slowed economic development, and the war-engendered rise to political prominence of the electrical engineers. The tsarist authorities, he argues, saw electrification as a "normal" technology, one that required no special or unusual treatment. The Soviet authorities, by contrast, grasped the key importance of political control over a "natural" monopoly on which Russian industrialization was based. Coopersmith shows how the Communist party, forging an alliance with engineers through the State Commission for the Electrification of Russia (GOELRO), harnessed the socially transforming power of this science-based enterprise. Despite the promotion of technological alternatives during the New Economic Policy, a centralized plan of electrification triumphed to the benefit of the Communist party and the detriment of local governments and the electrical engineers. Casting new light on the deep-seated and chronic conflict between the utopianism of Soviet ideology and the reality of Soviet politics and economics, this book will appeal to readers interested in the dynamics of Soviet society and comparative sociology, as well as to historians of science and technology.